Pediatric ventriculoperitoneal shunts and their complications: An analysis - Nitin Agarwal; Ram Mohan Shukla; Deepika Agarwal; Kaustubh Gupta; Rohtash Luthra; Jalaj Gupta; Sunny Jain (Wolters Kluwer Medknow Publications, 2017)
Introduction: Ventriculoperitoneal (VP) shunt is the most commonly utilized shunting procedure because of the capacity of the peritoneum to resorb fluid. Initial and subsequent peritoneal catheter placements can be done with relative ease. They are associated with a variety of complications. Materials and Methods: The total number of patients operated in the study period was 96. We studied 41 operated patients of VP shunt who had various shunt-related complications and analyzed the predisposing risk factors and spectrum of complications. Results: The mean age was 28 ± 32 months out of which 28 were males and 13 females. The etiology of hydrocephalus was aqueductal stenosis in 18, Arnold Chiari malformation in 10, Dandy-Walker malformation in 2, postmeningitis in 8 (pyogenic in 5 and tubercular in 3), postintraventricular hemorrhage in 2 patients and postencephalocele surgery in 1. Conclusion: With this retrospective review of complications of VP shunts, age at initial shunt insertion and the interval between the age of initial shunt placement and onset of complications were the most important patient-related predictors of shunt failure. The different predominant etiological factors responsible for early and late shunt failure were infective and mechanical complications, respectively.